2011
DOI: 10.1108/14779961111167676
|View full text |Cite
|
Sign up to set email alerts
|

The portable panopticon: morality and mobile technologies

Abstract: The purpose of this paper is to explore ethical issues arising from the mass deployment and take-up of mobile technologies. The ethical dimensions of mobile technologies and their use among the general population are considered within a conceptual framework drawing on James Moor's belief in a need for “better ethics” for emerging technologies and Michel Foucault's development of Jeremy Bentham's panopticon as a tool of surveillance. It is found that the mass deployment and use of mobile technologies amongst th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Instead we were positioned as active observers of a tool we had created and that was influencing our participants’ engagements with their personal technologies (the presence of the app on their smartphones, our knowledge of the content of the app and the different ways that the participants might interact with it). Indeed, this forms what De Saulles and Horner () have described as the “portable panopticon,” a digital version of Foucault's () notions of surveillance, whereby the smartphone becomes a space through which actions can be monitored and assessed. Here the smartphone becomes an apparatus of control through which behaviours are mediated virtually and anonymously.…”
Section: [Re]appropriating Technologies As “Research” Spacesmentioning
confidence: 94%
“…Instead we were positioned as active observers of a tool we had created and that was influencing our participants’ engagements with their personal technologies (the presence of the app on their smartphones, our knowledge of the content of the app and the different ways that the participants might interact with it). Indeed, this forms what De Saulles and Horner () have described as the “portable panopticon,” a digital version of Foucault's () notions of surveillance, whereby the smartphone becomes a space through which actions can be monitored and assessed. Here the smartphone becomes an apparatus of control through which behaviours are mediated virtually and anonymously.…”
Section: [Re]appropriating Technologies As “Research” Spacesmentioning
confidence: 94%
“…Today, the panopticon metaphor is so commonly applied that ‘the very mention of the term in conferences immediately leads scholars to roll their eyes in boredom’ (Caluya, 2010, p. 621). In response to its overuse, Haggerty (2006) argues for ‘tearing down the walls’ of the panopticon, assumedly along with transmorphisms such as the ‘superpanopticon’, ‘electronic panopticon’, ‘post-panopticon’, ‘ban-opticon’, ‘pedagopticon’, ‘fractal panopticon’, ‘synopticon’ and ‘neo-panopticon’ (Caluya, 2010; Haggerty, 2006), and more recently the ‘portable panopticon’ (De Saulles & Horner, 2011) which is enabled by mobile technologies.…”
Section: The Panopticon and Its Limitsmentioning
confidence: 99%
“…Discipline and Punish: The Birth of the Prison has proven to be a standard for this emerging and multidisciplinary field (Wood, 2003). The theory of panopticism is based on Jeremy Bentham's concept of a model prison from 1787, referred to as The Panopticon, and it was a method for enabling the few to monitor the actions of the masses and it has been used to describe the potential for centralised surveillance and the connotations of this on social control (de Saulls and Horner, 2011). Bentham's model consisted of a circular shaped building divided into cells and in the centre of this building, a high tower would be erected and would include wide windows to allow visibility and light into the cells.…”
Section: Filtering and Monitoringmentioning
confidence: 99%
“…Foucault examined this architectural model and transformed it into a theory for a disciplinary society based on the exercise of power through surveillance (de Saulls and Horner, 2011). He suggested that it could be used for additional purposes, rather than just prisons.…”
Section: Filtering and Monitoringmentioning
confidence: 99%